2022
DOI: 10.1101/2022.08.01.22278199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing, Tracing, and Vaccination Targets for Containment of the US Monkeypox Outbreak: A Modeling Study

Abstract: We estimate the levels of community testing, contact tracing, and vaccination required to reduce the effective reproduction number (Rt) of Monkeypox Virus (MPXV) below 1 for high risk men who have sex with men. We found that the critical threshold to vaccinate depends on the basic reproduction number of MPXV and on other public health measures. This analysis provides a framework for quantitative targets toward MPXV containment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
4
1
Order By: Relevance
“…This model enables the prediction of infectious waves that are not normally observed in standard SIR models: in terms of public health policies, this seems to suggest that particular attention is required to control the outbreak. The authors were also able to estimate the reproduction number for their model to be 2.31−2.66, which is, however, higher than our estimate and the value obtained by Du et al51 Chitwood et al53 devised a model focusing on the high-risk MSM population. The authors found that a robust public health response consisting of non-pharmaceutical interventions (i.e., testing and contact tracing) can be effective if at least 40% of human monkeypox cases are detected through community testing, and at least half of case contacts are traced.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…This model enables the prediction of infectious waves that are not normally observed in standard SIR models: in terms of public health policies, this seems to suggest that particular attention is required to control the outbreak. The authors were also able to estimate the reproduction number for their model to be 2.31−2.66, which is, however, higher than our estimate and the value obtained by Du et al51 Chitwood et al53 devised a model focusing on the high-risk MSM population. The authors found that a robust public health response consisting of non-pharmaceutical interventions (i.e., testing and contact tracing) can be effective if at least 40% of human monkeypox cases are detected through community testing, and at least half of case contacts are traced.…”
contrasting
confidence: 77%
“…Chitwood et al 53 devised a model focusing on the high‐risk MSM population. The authors found that a robust public health response consisting of non‐pharmaceutical interventions (i.e., testing and contact tracing) can be effective if at least 40% of human monkeypox cases are detected through community testing, and at least half of case contacts are traced.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In a US model in a scenario with modest public health response (20% of community cases detected and 25% of cases traced), the critical threshold ranged from 5% to 43% (assuming 100% vaccine efficacy). [24] Our study’s estimate of vaccine uptake may inform further mathematical modeling to understand outbreak dynamics and effect of vaccines in more depth.…”
Section: Discussionmentioning
confidence: 93%
“…The global mpox outbreak of 2022-2023 was primarily driven by sexual transmission within MSM networks (5). With limited spillover to the broader general population, the 2022 outbreaks predominantly affected high-risk MSM communities (6,7), making these communities primary targets for subsequent vaccination campaigns (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The global mpox outbreak of 2022-2023 was primarily driven by sexual transmission within MSM networks (5). With limited spillover to the broader general population, the 2022 outbreaks predominantly affected high-risk MSM communities (6,7), making them primary targets for subsequent vaccination campaigns (8,9). The global transmission in 2022 was evident, but it was not until 2023 when Western Pacific nations, including Japan, South Korea, and Taiwan, saw significant case counts (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%